Effective Leadership Models for Generation Z in the Healthcare Sector: A Contextual Analysis in ASEAN Countries - Arvi Iskandar; Muhardi Muhardi; Nunung Nurhayati; Hardy Hutahaean; Dede R Oktini (International Journal of Economics, Commerce, and Management, 2025)
Demographic changes and the acceleration of digital transformation have presented new challenges in leadership practices, especially in the healthcare sector of ASEAN countries. Generation Z, who grew up in a digital environment, brings different values and preferences to leadership styles. This study aims to identify the leadership model that best suits the characteristics of Gen Z in the context of healthcare, as well as analyze the contextual factors that influence it in the Southeast Asian region.This study uses a qualitative approach based on literature studies from various academic publications and empirical findings in ASEAN countries. Data are analyzed thematically to reveal the leadership patterns that are most relevant to the needs of Gen Z in the health sector.The study results show that transformational, participatory, and digital-based leadership styles are more effective for leading Gen Z healthcare workers. This generation rejects leadership models that are tightly controlled or micromanaged, and prefers leaders who support autonomy, collaboration, and innovation. Local cultural factors, such as traditional values and social collectivity, also reinforce the importance of adapting leadership styles to diverse cultural contexts. Leadership success is also greatly influenced by the leader's ability to bridge cross-generational differences and manage communication effectively.These findings contribute to the development of a generationally and contextually relevant leadership model, as well as serve as a reference in formulating HR development strategies and leadership training programs in multigenerational health organizations in Southeast Asia.